Detailed Fluid Inclusion and Stable Isotope Analysis on Deep Carbonates from the North Alpine Foreland Basin to Constrain Paleofluid Evolution - Elena Mraz; Markus Wolfgramm; Inga Moeck; Kurosch Thuro (Geofluids)
The recent interest on environmentally friendly energy resources has increased the economic interest on the Upper Jurassic carbonate rocks in the North Alpine Foreland Basin, which serves as a hydrogeothermal reservoir. An economic reservoir use by geothermal fluid extraction and injection requires a decent understanding of porosity–permeability evolution of the deep laying Upper Jurassic strata at depths greater than 2000 m. The analysis of paleofluids caught in cements of the rock mass helps to determine the postdepositional reservoir evolution and fluid migration. Therefore, the high- and low-permeability areas of the Upper Jurassic in the North Alpine Foreland Basin referred to as Molasse Basin were analyzed by means of encountered postdepositional cements to determine the reservoir evolution. The cements were sampled at different hydrocarbon and geothermal wells, as well as at outcrops in the Franconian and Swabian Alb. To determine the composition and temperature of the paleofluids, fluid inclusions and cements of the Upper Jurassic carbonate rocks were analyzed by microthermometry and stable isotope measurements. Since drill cuttings are a rather available sample material compared to drill cores, a new microthermometry measurement method was achieved for the around 1 mm drill cuttings. Salinity and formation temperature of paleofluids in fluid inclusions and isotope data are consistent with previous studies and reveal a 5-stage evolution: the main cementation phases are composed of (I) the early diagenesis in limestones (200-400 m, 40-50°C), (II) early diagenetic dolomitization, and (III) burial dolomitization (1-2 km, II: 40-90°C; III: 70-100°C; 40 g/L NaCl equiv.), and (IV) late burial calcification (IIIa: 110-140°C, IIIb: 140-200°C) linked to tectonic features in the Molasse Basin. In the outcrop samples, a subsequent (V) cementation phase was determined controlled by karstification. In the southwest, an increase in salinity of the fluid inclusions in vein calcites, above the salinity of the Jurassic seawater, highlights the influence of basin fluids (diagenetic, evaporitic). In the other eastern wells, vein calcites have precipitated from a low saline fluid of around 10-20 g/L NaCl equiv. The low salinity and the isotope values support the theory of a continuous influence of descending meteoric fluids. Consequently, the Upper Jurassic seawater has been diluted by a meteoric fluid to a low saline fluid (<1 g/L), especially in areas with high permeability. Here, we show how a better understanding of cementation trajectory at depth can help to generate a better understanding of geothermal usability in deep carbonate reservoirs.